SRI funds: Nomen est omen - Alexander Kempf; Peer Osthoff (University of Cologne, Centre for Financial Research (CFR), 2007)
We test the frequently made claim that SRI funds are conventional funds in disguise. For this purpose, we compare the portfolio holdings of SRI funds to conventional funds concerning their social and environmental standards. Our empirical study of US equity funds shows that SRI funds have a significantly higher ethical ranking than standard funds, i.e., they are not conventional funds in disguise. This result holds for all ethical criteria we investigate. It is stable over time and holds after controlling for several fund characteristics. Finally, we find no evidence that our result is generated by window dressing strategies of SRI funds.
Keywords: G11; G20; M14; 330; Socially Responsible Mutual Funds; Socially Responsible Investing; Ethical Investment